Biodegradable Zein-Based Blend Films: Structural, Mechanical and Barrier Properties (2015)
ABSTRACT: The effect of adding a hydrocolloid on the structural, mechanical and barrier properties of zein-based blend films is evaluated. Zein-oleic acid blend fi lm with added xanthan gum (Z-OA-XG) showed higher water solubility (13.09 %) and opacity (8.49 AU/mm) than zein-oleic acid (Z-OA) fi lm (10.80 % and 5.19 AU/mm, respectively). Furthermore, Z-OA film had greater flexibility with lower Young’s Modulus (YM=5.02 MPa) and higher elongation at break (η=10.62 %); nonetheless, it was less resistant to tension (tensile strength σ=8.5 MPa) than Z-OA-XG fi lm, which showed YM, η and σ of 6.38 MPa, 6.66 % and 10.485 MPa, respectively. Both films had glossy and homogeneous structure with comparable water vapour and oxygen barrier properties around 4.39·10–11 and 1.82·10–13 g/(Pa·s·m), respectively. Based on that, xanthan gum structure influenced mainly mechanical and light barrier properties of zein-oleic acid blend films.